The impact of brain science literacy on creative thinking: a meta-analytic study - Peng, Qirong; Ma, Yan; Zhang, Lu; Zhou, Ruyu (Frontiers in Education, 2025)
IntroductionCreative thinking is essential for developing high-level innovative talents. However, its underlying neuroplastic mechanisms and effective educational interventions remain underexplored.MethodsThis meta-analysis synthesizes data from 35 experimental studies (N = 14,688) to examine the effects of brain science literacy on creative thinking and its potential moderators.ResultsThe results indicate that brain science literacy has a small but significant positive effect on creative thinking (g = 0.20, p = 0.003), with stronger effects observed in teaching strategy optimization (g = 0.32), student behavioral regulation (g = 0.37), and early childhood interventions (g = 0.70). The impact on originality (g = 0.53) was significantly stronger than on fluency (g = 0.20) and the overall creativity score (g = 0.26). The intervention effects varied across educational stages, with the most substantial benefits seen in early childhood (g = 0.70) and at the university level (g = 0.30).DiscussionThese findings suggest that improving brain science literacy can promote neuroplasticity and enhance creative thinking, with varying effects across developmental stages and creative components. The benefits observed in early childhood highlight the critical importance of brain science literacy-informed educational interventions during sensitive periods of cognitive development. This study provides solid empirical support for integrating neuroscience principles into educational practice, offering practical guidance for educational policy and curriculum design. Overall, brain science literacy appears to foster creativity through a dual pathway: neuroplasticity activation and developmental stage adaptation, presenting a focused framework for evidence-based neuroeducational interventions.